Relationships among Drought Tolerance Indices and Yield Characters of Cowpea (Vigna unguiculata L. Walp) - Ajayi, Abiola Toyin (International Journal of Scientific Research in Biological Sciences, 2020)
Drought is an abiotic factor capable of stunting cowpea (Vigna unguiculata L. Walp) productivity. Hence, genetic variation, heritability and interrelationships of leaf relative water content (RWC), yield characters and drought tolerance indices (DTIs) were examined in 24 genotypes of cowpea in the screen house in pots under two watering regimes; 500 ml/pot daily and once in 10 days for control and drought stress, respectively. For all traits, there were substantial variations amongst genotypes, treatments and their interaction. Genotypes also differed significantly for all the DTIs. DTIs and all traits in both conditions had high heritability (>60%) except RWC and seeds/pod under control. Genetic gain (GAM) was high (>20%) for all traits and DTIs except RWC under control, making selection for these traits and indices effective. PCA and biplot of PCs 1 and 2 accounted for 75.5% of the total variability with important contributors (loadings > 0.40) like pods/plant, seeds/plant and seed yield in both conditions and DTIs included in PCs 1 and 2. Genotypes G20, G19 and G11 were considered the best in terms of yield above average (>18.94 g) in control and (>3.98 g) under drought stress, while G2 was more stable (13.79 g and 10.71 g) under both conditions. PCA, biplot and Pearson correlation affirmed that the top indices for pinpointing drought tolerant cowpea genotypes were STI, GMP, YI, YSI and DRI. Although seed yield under control condition was not correlated with seed yield under drought stress, under both conditions, GMP and STI had positive correlation with seed yield as well as with YSI, YI and DRI